Answer: [tex]Expression = 6[/tex] Step-by-step explanation: Given [tex]\frac{36p}{6p}[/tex] Required Express in standard form [tex]Expression = \frac{36p}{6p}[/tex] Divide both sides of the fraction by p [tex]Expression = \frac{36}{6}[/tex] Divide both sides of the fraction by 6 [tex]Expression = \frac{6}{1}[/tex] [tex]Expression = 6[/tex] Log in to Reply

Answer:[tex]Expression = 6[/tex]

Step-by-step explanation:Given[tex]\frac{36p}{6p}[/tex]

RequiredExpress in standard form

[tex]Expression = \frac{36p}{6p}[/tex]

Divide both sides of the fraction by p[tex]Expression = \frac{36}{6}[/tex]

Divide both sides of the fraction by 6[tex]Expression = \frac{6}{1}[/tex]

[tex]Expression = 6[/tex]